Physiological parameters of dental fear and anxiety in adults related to surgical extraction of impacted third molars - Selimović Edin; Bajrić Elmedin (Balkan Stomatological Society, 2024)
Background/Aim: Dental fear and anxiety (DFA) are psychological phenomena normally arising and developed in the dental office during various kinds of dental procedures and interventions. The most usual stressors for the DFA appearance are those related to dental pain, no matter if the pain has already been caused, or potentially will be committed. There are a few main dental pain-provoking factors related to endangering body integrity in the oral cavity, and tooth extraction is the strongest one. The research aimed to observe, notify, and analyze physiological parameters of DFA in adults related to oral surgical therapy procedures of removing impacted third permanent molars. Material and Methods: After inclusive selection 500 patients entered into the study. The study protocol included preoperative assessment of DFA presence with Corah's Dental Anxiety Scale (CDAS) on examination day, preoperative assessment of physiological parameters on examination day and operative day before the treatment, as well as their postoperative assessment followed by evaluation of postoperative pain, on the day after the treatment. Results: The results of our research indicated that an increase in DFA led to increased values of the measured physiological parameters for all preoperative measurement days. The postoperative decrease in the physiological parameters values could be explained by the fact that the oral-surgical procedure was completed, so the psychological burden of the patients was also less. Conclusions: Patients with higher values of the DFA presence have also declared more postoperative pain.